Super typhoon Rai (Odette) track forecasting and democratizing risk communication - Caimbre, Katherine Joy D.; Casas, Eulito V. (2024)
The Philippines faces an annual average of 6 to 9 typhoons, underscoring the imperative of timely and accurate tropical cyclone forecasts to promote early public awareness and preparedness. Leveraging a high- resolution approach with a grid size of 2.5km, the Cloud-Resolving Storm Simulator (CRESS) employs the National Centers for Environmental Prediction (NCEP) Global Forecast System (GFS) to analyze the dynamics of Super Typhoon Rai (2021). The forecasted track and intensity of Super Typhoon Rai generated by CRESS serve as foundational elements for a relational model aimed at democratizing risk communication practices. Examination of the hindcasts for Super Typhoon Rai unveils notable enhancements in pre-landfall track and intensity, particularly evident at 0060 UTC on December 14 (118.2 knots) and 1800 UTC on December 13 (117.4 knots). Additionally, the findings underscore the efficacy of narrative-based communication designs in fostering evacuation intent, self-relevance, trust, clarity, and perceived authority of the communication source. Furthermore, the study investigates the factors contributing to the disregard of evacuation warnings by individuals. Rooted in contemporary research on evacuation behavior and emergency preparedness for extreme hazard events, the relational model advocated in this study aligns with broader initiatives aimed at democratizing risk communication and empowering individuals to take proactive measures in response to such occurrences.
Master's thesis (M.S. E.S.) -- University of the Philippines, Tacloban.